2013
DOI: 10.1177/194008291300600607
|View full text |Cite
|
Sign up to set email alerts
|

The Thin-Spined Porcupine, Chaetomys Subspinosus (Rodentia: Erethizontidae), within Protected Areas in the Atlantic Forest, Brazil: Local Knowledge and Threats

Abstract: The thin-spined porcupine, Chaetomys subspinosus, is an endemic mammal of the Atlantic forest of northeastern Brazil. With its population declining, it has been listed as "vulnerable" in the Brazilian Red List. Its National Action Plan, published in 2011, intended to develop awareness projects about the species in local communities, to implement alternative income projects and protein consumption, and to evaluate hunting pressure. This study investigates rural residents' knowledge of the thin-spined porcupine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Therefore, it makes sense that people, who are not in constant movement to and from the forest, encounter L. latrans more often, since the frog itself moves more and it lives well in man-disturbed habitats. All men interviewed are frequently shifting from one place to another and transiting throughout the forest more than women, as has already been reported elsewhere (Castilho et al 2013), thereby increasing the probability of observing species with a smaller home range, such as P. burmeisteri. Fernandes-Ferreira et al (2013) also identified two species used for these purposes by a community from the same region: Leptodactylus vastus (Leptodactylidae) for food, which happened to be the genus reported for this same use in the present study and Rhinella jimi (Bufonidae).…”
Section: Id*mentioning
confidence: 63%
See 1 more Smart Citation
“…Therefore, it makes sense that people, who are not in constant movement to and from the forest, encounter L. latrans more often, since the frog itself moves more and it lives well in man-disturbed habitats. All men interviewed are frequently shifting from one place to another and transiting throughout the forest more than women, as has already been reported elsewhere (Castilho et al 2013), thereby increasing the probability of observing species with a smaller home range, such as P. burmeisteri. Fernandes-Ferreira et al (2013) also identified two species used for these purposes by a community from the same region: Leptodactylus vastus (Leptodactylidae) for food, which happened to be the genus reported for this same use in the present study and Rhinella jimi (Bufonidae).…”
Section: Id*mentioning
confidence: 63%
“…Our data indicate that men seem to have more knowledge on potential uses for amphibians than women. This seems plausible because men (as mentioned by themselves) have more frequent contact with their natural surroundings in low-income rural societies in the region, as they have to walk to their working places every day, when they need to deal with the forest tasks, whereas women and children mostly pass their days near their homes due to domestic affairs (Castilho et al 2013). Despite this, both groups mentioned almost the same species.…”
Section: Id*mentioning
confidence: 98%
“…Edge effects favor liana and pioneer species proliferation (Laurance et al 2002), 2 resources largely used by thin-spined porcupine. With these biological characteristics, conservation efforts aimed at preserving and increasing forest remnant connectivity could provide structural and functional landscapes (see Lidicker 1999) and potentially increase longterm persistence, providing that other disturbances such as hunting (Castilho et al 2013) and fire (Faria et al 2011) are under control.…”
Section: Model Rankmentioning
confidence: 99%
“…This medium-sized (1.3-2.7 kg) rodent species (Chiarello et al 1997;Oliveira et al 2012) is nocturnal, arboreal and folivorous (De Souto Lima et al 2010;Giné et al 2010;Giné et al 2012;Oliveira et al 2012). It is also opportunistically hunted by local people mainly for the meat (Castilho et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hunters describe Chaetomys as less well defended than the sympatric porcupine, Coendou insidious, because Chaetomys is slower, its quills are softer and don't come loose when an aggressor attacks (Castilho et al 2013). The barbless quills are tan, relatively thick and short on the head, neck and upper back; farther back on the sides and rump, they are long and slender suggesting that the pelage of most of the back does not contribute to the physical defense of the animals (Giné et al 2012;Giné personal communication 2015).…”
Section: Introductionmentioning
confidence: 99%